Pengenalan Metode Pembayaran Cash On Delivery (COD) Dalam Kegiatan Transaksi Belanja Online Pada Warga Dusun II Desa Sidoluhur - Suhardi, Mutia Aprizki; Febliansa, M. Rahman; Anzori, Anzori; Damarsiwi, Eska Prima Monique (Universitas Dehasen Bengkulu, 2023)
Most people often make payments using the Cash On Delivery method, but there are still many who don't know what Cash On Delivery really means. Some people are more familiar with the acronym than the practice of Cash On Delivery itself, blaming the courier as the party responsible for the shortage or error of the goods they ordered. Sidoluhur village is located in Sukaraja district, Seluma district, Bengkulu province. Many residents in Hamlet II of Sidoluhur Village still do not understand this problem. Therefore, efforts that can be made are by conducting an introduction which on this occasion is packaged in the form of a PKM activity with the title